Pengaruh Kepuasaan Orang Tua dan Kualitas Layanan Pendidikan terhadap Jumlah PPDB di SMPIT Al Mawaddah Warrahmah Kolaka - Dzakiyyah Nur An Nasjwa; Sulkifli Ar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to analyze the influence of parental satisfaction and educational service quality on the number of new student admissions at SMPIT Al Mawaddah Warrahmah Kolaka. This research employs a quantitative associative approach. The population consists of 120 parents of students in the 2024/2025 academic year, with a sample of 92 respondents selected using a proportionate stratified random sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 25. The results show that parental satisfaction and educational service quality simultaneously have a significant effect on new student admissions, as indicated by an F-value of 17.736 with a significance level of 0.001 (< 0.05). The coefficient of determination (R²) of 0.780 indicates that 78% of the variation in new student admissions can be explained by the two variables, while the remaining 22% is influenced by other factors outside the model. These findings suggest that higher parental satisfaction and better educational service quality increase the community’s interest in enrolling their children at SMPIT Al Mawaddah Warrahmah Kolaka.